Lewensstories van getroude vroue: "n Moontlikheid tot transformasie - Botha, Annelie (HTS teologiese studies, 2015)
Life stories of married woman: A possibility to transformation. Feminist scholarship in various disciplines has shown that women tend to internalise dominant social and religious discourse with regard to their lesser worth and value as human beings and members of society. The focal point of this article is to demonstrate how the place and role allocated to women, specifically in marital relationships, can be experienced as harmful. This article makes use of the life history research method in combination with the emancipatory analysis model of Elisabeth Schüssler Fiorenza in order to demonstrate this. Interviews were done with five women of the Netherdutch Reformed Church of Africa, a fairly conservative and traditional Afrikaans speaking South African faith community. In spite of having lived with this mindset all of their lives, the women were able to express in which ways they experienced the dominant discourse as harmful. If social and religious views devalue a certain group of people, transformation is required. In the case of women, respectfully listening to their life stories and experiences can contribute to their own healing as well as to the transformation of their social and religious environment and the practice of the church.